Anti-allergic effect of Artemisia extract in rats - Deng, Yan (Exp Ther Med, 2016)
Artemisia apiacea (also known as Artemisia annua L) is a herb commonly used in traditional Chinese medicine. In the early 1970s, artemisinin was isolated and identified as the active antimalarial ingredient, and thereafter, A. apiacea and artemisinin have been studied extensively, such as anti-inflammation and antipyresis, antibacteria, antiparasitic and immunosuppression effects of A. apiacea extract. The present study investigated the extracts anti-allergic effect obtained from the dried flowering tips of A. apiacea in rats. A systemic anaphylactic reaction model was induced in rats using compound 48/80. Artemisia extract was administered 1 h prior to the injection of compound 48/80. Artemisia was extracted from dried flowering tips of A. deserti using 80% ethanol. Subsequently, the systemic anaphylactic shock, histamine release, scratching behavior and vascular permeability induced by compound 48/80 were evaluated. The administration of Artemisia extract at 200 and 400 mg/kg doses suppressed the systemic anaphylactic shock induced by compound 48/80 in a dose-dependent manner. Overall, the Artemisia extract was able to effectively decrease systemic anaphylactic shock, histamine release, scratching behavior and vascular permeability induced by compound 48/80 in a dose-dependent manner.